Decreased expression of FOXP3 in nasal polyposis - Kannika Roongrotwattanasiri (2018)
Purpose: The pathogenesis of nasal polyposis (NP) is unclear. Eosinophils and mast cells are considered to play important roles in this process. In addition, the levels of Th2-type cells are increased, irrespective of the atopic status of the patient with NP. In this context, we and others have shown high levels of thymus and activation-related chemokine/CCL17, macrophage-derived chemokine, eotaxin, and RANTES in patients with NP. Forkhead box P3 (FOXP3) plays a key role in CD4+CD25+ regulatory T-cell function and represents a specific marker for regulatory T cells (Tregs). Decreased expression of FOXP3 has been reported in allergic diseases. The present study was designed to evaluate the presence and potential roles of Tregs, defined by the expression of FOXP3 protein, in NP. Methods: Using immunohistochemistry, we estimated the numbers of FOXP3+ cells in the epithelium and lamina propria of the NPs of 17 patients with chronic rhinosinusitis with NP and the nasal mucosa of 15 patients with allergic rhinitis (AR). The number of FOXP3+ cells in NPs was compared with that in the nasal mucosa of patients with AR, and the numbers of FOXP3+ cells in atopic and non-atopic NP were also compared. Results: The number of FOXP3+ cells in the lamina propria of patients with NP was significantly lower than that in the nasal mucosa of the AR patients (2.79 vs. 5.99, P=0.008). There was no statistically significant difference noted for the numbers of FOXP3+ cells between the epithelium of the NP and the nasal mucosa (3.60 vs. 2.39, P=0.180). Furthermore, the numbers of CD4+FOXP3+ cells were lower in NPs than in the allergic nasal mucosa. There was no difference in the number of FOXP3+ cells between the atopic and non-atopic NP patients. Conclusions: Fewer Tregs (i.e., decreased FOXP3 expression) are found in NPs than in the nasal mucosa of AR patients. As the severity of eosinophilic, Th2-type inflammation and the levels of inflammatory mediators are much higher in NPs than in the nasal mucosa of AR patients, an inverse co-relationship may exist between these parameters and the number of Tregs. The deficiency of Tregs in NP may account for the more pronounced Th2-type inflammation seen in these patients. © The Korean Academy of Asthma, Allergy and Clinical Immunology.